Effect of granulocyte colony stimulating factor (G-CSF) on IVF outcomes in infertile women: An RCT - Maryam Eftekhar; Robabe Hosseinisadat; Ramesh Baradaran; Elham Naghshineh (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Despite major advances in assisted reproductive techniques, the implantation rates remain relatively low. Some studies have demonstrated that intrauterine infusion of granulocyte colony stimulating factor (G-CSF) improves implantation in infertile women. Objective: To assess the G-CSF effects on IVF outcomes in women with normal endometrial thickness. Materials and methods: In this randomized controlled clinical trial, 100 infertile women with normal endometrial thickness who were candidate for IVF were evaluated in two groups. Exclusion criteria were positive history of repeated implantation failure (RIF), endocrine disorders, severe endometriosis, congenital or acquired uterine anomaly and contraindication for G-CSF (renal disease, sickle cell disease, or malignancy). In G-CSF group (n=50), 300 μg trans cervical intrauterine of G-CSF was administered at the oocyte retrieval day. Controls (n=50) were treated with standard protocol. Chemical, clinical and ongoing pregnancy rates, implantation rate, and miscarriage rate were compared between groups. Results: Number of total and mature oocytes (MII), two pronuclei (2PN), total embryos, transferred embryos, quality of transferred embryos, and fertilization rate did not differ significantly between two groups. So there were no significant differences between groups in chemical, clinical and ongoing pregnancy rate, implantation rate, and miscarriage rate Conclusion: our result showed in normal IVF patients with normal endometrial thickness, the intrauterine infusion of G-CSF did not improve pregnancy outcomes.